2005
DOI: 10.1152/ajpgi.00295.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fat absorption in cystic fibrosis mice is impeded by defective lipolysis and post-lipolytic events

Abstract: Cystic fibrosis (CF) is frequently associated with progressive loss of exocrine pancreas function, leading to incomplete digestion and absorption of dietary fat. Supplementing patients with pancreatic lipase reduces fat excretion, but it does not completely correct fat malabsorption, indicating that additional pathological processes affect lipolysis and/or uptake of lipolytic products. To delineate the role of such (post) lipolytic processes in CF-related fat malabsorption, we assessed fat absorption, lipolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 42 publications
8
65
2
Order By: Relevance
“…The low levels of serum albumin and triglycerides in the CF mice of this study indicates a compromised nutrition level and reduced lipid absorption (20), both of which were ameliorated by rhIGFBP-3 treatment. A positive association between increased IGFBP-3 levels and each of serum triglycerides (34) and albumin levels (35) has been reported, but a causal mechanism linking these measures, if such exists, is unknown.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The low levels of serum albumin and triglycerides in the CF mice of this study indicates a compromised nutrition level and reduced lipid absorption (20), both of which were ameliorated by rhIGFBP-3 treatment. A positive association between increased IGFBP-3 levels and each of serum triglycerides (34) and albumin levels (35) has been reported, but a causal mechanism linking these measures, if such exists, is unknown.…”
Section: Discussionmentioning
confidence: 67%
“…As an assessment of the nourishment level in these mice serum albumin was assayed and as previous studies report lower serum triglycerides in CF mice (4,20), we determined whether the treatment affected this phenotype. The serum levels of albumin and triglycerides were found to be lower in CF compared with WT mice (p ϭ 0.0007 and p ϭ 0.02, respectively) and to increase by administration of rhIGFBP-3 in CF mice (p ϭ 0.03 and p ϭ 0.015, respectively; Fig.…”
Section: Expression Of Igf Pathway Genes Is Altered In Intestines Of mentioning
confidence: 99%
“…CF mice have severe gastrointestinal disease (16,17) and CF mice with a null Cftr mutation have lipid malabsorption (36). We speculate that loss of Cftr function results in intestinal epithelial cell dysfunction, including altered fluid and electrolyte transport, but also malabsorption in this tissue.…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 89%
“…To quantify this phenomenon, an important area of future research would be to measure total fecal energy losses in CF mice. Since the CF mouse has minor pancreatic disease (16,36), this experiment would help elucidate the role of primary intestinal disease on malabsorption and growth.…”
Section: Growth In Cystic Fibrosis Micementioning
confidence: 99%
“…Bijvelds et al also revealed that cftr null mice showed similar increased fat excretion and fecal bile salt loss. 24) Similar to that observed in the bile ducts, functional defects in CFTR might occur in the intestine. This may lead to intestinal malabsorption of bile acids in Vil2 kd/kd mice, as has been reported in cystic fibrosis (CF) patients.…”
Section: Vil2mentioning
confidence: 68%